Romani Women in the 21st Century and the Role of their Position for Children’s Upbringing - Farkašová, Monika (Wydawnictwo Naukowe UAM, 2015)
This paper deals thematically with the emancipation of Romani women in the Slovak Republic, their position in the society, as well as delimitation of their social status and role. Emphasis is put on differences in culture, cultural patterns and behavioral models, differences in the upbringing of children and the position of the Romani woman in the Romani family, compared to the society’s majority. Obstacles to the formation of an independent and emancipated Romani woman are described, for whom the concepts of emancipation and equality of rights are unknown and nearly inconceivable. Emancipation and equality of Romani women is particularly relevant in terms of opportunities for education, employment, position in the society and awareness of one’s rights. The objective is to present educated, successful, independent, and equal Romani women, enlightenment amongst the Romani population, engagement of Romani women in public and social life, and support them through various projects, etc.
Keywords: Emancipation of women; Education; Culture; Enlightenment; Romani communities; Majority society